The development and evaluation of the qualities of thinking skills module - Tee Tze Kiong, Azhari Azman Mohamed Nor, Md Yunos Jailani, Yee Mei Heong, Mohamad Mimi Mohaffyza, Mohamad Baharom, Othman Widad, (N/A, 2013)
The development and evaluation of the qualities of thinking skills module by Tee Tze Kiong, Azhari Azman Mohamed Nor, Md Yunos Jailani, Yee Mei Heong, Mohamad Mimi Mohaffyza, Mohamad Baharom, Othman Widad,